2014
DOI: 10.1016/j.jaac.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns of Cortisol Regulation Differ in Maltreated and Nonmaltreated Children

Abstract: Objective Child maltreatment is associated with dysregulation of stress-mediating systems and an increased risk of mental and physical health problems. Specifically, disruptions in hypothalamic-pituitary-adrenal (HPA) axis regulation have been reported in maltreated children. The current study investigates whether increased cortisol variability is responsible for inconsistent patterns in the literature. Method This study modeled cortisol activity over 20 weeks in 187 maltreated and 154 nonmaltreated children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 33 publications
1
61
1
Order By: Relevance
“…Future research may also benefit from incorporating other factors that may influence the clinical impact of various patterns of trauma exposure, such as the age at which a trauma occurred, the recency of trauma, gender, type of maltreatment, and other environmental and child factors. Research has shown that this heterogeneity within exposure to adversities is critical in predicting clinical outcomes (e.g., Doom et al, 2014; Busso, McLaughlin, & Sheridan, 2016), demonstrating that children who experience the same event do not necessarily experience the same outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Future research may also benefit from incorporating other factors that may influence the clinical impact of various patterns of trauma exposure, such as the age at which a trauma occurred, the recency of trauma, gender, type of maltreatment, and other environmental and child factors. Research has shown that this heterogeneity within exposure to adversities is critical in predicting clinical outcomes (e.g., Doom et al, 2014; Busso, McLaughlin, & Sheridan, 2016), demonstrating that children who experience the same event do not necessarily experience the same outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis is particularly susceptible to environmental contexts (Doom, Cicchetti, & Rogosch, 2014). For example, Ockenfels et al (1995) found steeper diurnal slopes for cortisol in the context of unemployment stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these studies, the specific type of maltreatment (e.g. abuse or neglect or both) was not specified (Doom et al, 2014; Trickett et al, 2010). These convergent results in both humans and NHP suggest a temporal switch from hypercorticolism to hypocortisolism.…”
Section: Cross-species Success Storiesmentioning
confidence: 99%